Prozaiczna codzienność superbohaterów, czyli analiza komiksowej serii Karla Ferdona - Czaja, Justyna (Załącznik Kulturoznawczy, 2023)
The Prosaic Everyday Life of Superheroes, or Some Remarks About Karl Ferdon’s Comic Series The article discusses a parody comic series by Chilean cartoonist Karlo Ferdon which depicts American superheroes in prosaic day-to-day situations. The author shows how placing iconic pop culture characters in an unexpected context can lead to their deconstruction and demythologization.